KEOTENTIKAN AKTA JAMINAN FIDUSIA YANG TIDAK DITANDATANGANI DI HADAPAN NOTARIS - Sudiharto Sudiharto (Jurnal Pembaharuan Hukum, 2015)
The Fiduciary Guaranty Act (AJF) must be made in authentic form and AJF registration must be performed online. This article is for identifying and answering unsigned fiduciary deed issues in the presence of Notary and registration of fiduciary guarantee deeds conducted online. Article 5 Paragraph (1) of Law Number 42 Year 1999 regarding Fiduciary Guaranty, explains “The imposition of objects with Fiduciary Guarantee is made by notary deed in the Indonesian language and is a deed of Fiduciary Guarantee.”The notarial deed, hereinafter referred to as Deed, is regulated in Article 1 number 7 of Law Number 2 Year 2014 regarding Amendment to Law Number 30 of 2004 concerning Notary Position, is an authentic deed made by or in the presence of Notary according to the form and procedure stipulated In this Act.The fiduciary guarantee deed is a partial deed, the deed made before the Notary Public, in practice the Notary is referred to as the party deed. The contents of the party’s deeds are a description or description, statements of the parties given or told before a Notary. The parties wish that their description or statement be poured into the form of Notary deed. Thus, the notary in this case reads and witnesses the signing made before him. Facing intended that the deed is done “reading” and “signing” in front of a notary, as a general official.The purpose of this study to be some of these problems. Method Approach is done Sociological Juridical Method with qualitative data analysis. Technique of data collecting is done by Study of Literature and Interview. The results of the research indicate that the fiduciary guarantee certificate that is made is not in accordance with Article 1868 of the Criminal Code signed in the presence of a Notary having the power to prove the deed under the hand. Moderate certificates issued by Online registration are considered lawful.